Differentiation of Andean and Mesoamerican accessions in a proposed core collection of grain amaranths - Blair, Matthew W.; Londoño, Jorge M.; Buitrago-Bitar, María A.; Wu, Xingbo; Brenner, David M. (Frontiers in Plant Science, 2023)
Grain amaranths are made up of three New World species of pseudo-cereals with C4 photosynthesis from the dictotyledenous family Amaranthaceae and the genus Amaranthus. They originate in two ecoregions of the Americas, namely the inter Andean valleys of South America and the volcanic axis and lowlands of Mexico and Central America. These correspond to two centers of domestications for Andean and Mesoamerican crops, with one cultivated species found in the first region and two found in the latter region. To date, no core collection has been made for the grain amaranths in the USDA germplasm system. In this study, we propose a core for the 2899 gene bank accessions with collection site data. We constituted the core with 260 genotypes of Amaranthus which we evaluated with 90 single nucleotide polymorphism markers. Our goal was to distinguish between Andean and Mesoamerican genepools of amaranths, including the cultivated species and three possible progenitor or wild relative ancestors along with two more species in an outgroup. Population structure, clustering and discriminant analysis for principal components showed that Andean species, A. caudatus and A. quitensis shared fewer alleles with Mesoamerican species, A. cruentus and A. hypochondriacus, compared to each group individually. A. hybridus was a bridge species that shared alleles with both regions. Molecular markers have the advantage over morphological traits at quickly distinguishing the Andean and Mesoamerican cultivars and have the added benefit of being useful for following inter-species crosses and introgression.